Ethical ideas of Heorhii Ivanovych Chelpanov: to the history of University of St. Volodymyr - V. G. Napadysta (Ukrainian Cultural Studies, 2020)
The article examines the ethical ideas in the creative heritage of H.I. Chelpanov, a Professor at St. Volodymyr University, a well-known scientist at the time, the founder of scientific institutions, who actively promoted the spread and deepening of philosophical culture among students and popularized topical ethical issues in public. Although the scientist paid more attention to psychology, it goes unnoticed that moral issues remain cross-cutting in all his works: articulation on the basis of ethics for other fields of scientific knowledge is obvious. H.I. Chelpanov’s research interest was mainly focused on the problem of free will, which seems to be dominant in his ethical interests and the definition of value foundations in the vision of human life. According to the scientist, justifying the free will of man in a causally dependent world is extremely difficult and, at the same time, extremely important for the recognition of the highest values of humanity. In his view of free will, the decisive factor is not its causality but human responsibility for hisactions. The solution of the free will problem for H.I. Chelpanov was possible only in the sphere of morality. Only from this position could free will be protected with the preservation of the original content. Because the problem of free will is solved for moral purposes, it can be solved regardless of whether the issue of causality is resolved. Freedom of will, therefore, he deduced from the sense of responsibility. H.I. Chelpanov not only justified the existence of free will, but also reflected on the ways to achieve it, because, in his opinion, freedom of will is not an original gift, but emerges as a result of hard work of the individual, which, in turn, opens opportunities to change and improve the personality, if desired. H.I. Chelpanov was an implacable opponent of the great European "pessimists" – A. Schopenhauer and E. Hartmann, defended the groundlessness of fatalistic predictions about the moral development of both the individual and humanity as a whole.